الحرمان من عاطفة الأبوين وعلاقته بالسلوك العدائي لدى المراهقين (University of Mosul-college of Basic Education, 2010)
هدف البحث إلى قياس مستوى الحرمان العاطفي، وقياس مستوى السلوك العدائي لدى طلبة المرحلة الإعدادية. فضلا عن التعرف على العلاقة بين درجة الحرمان العاطفي والسلوك العدائي، والكشف عن الفرق في معامل الارتباط تبعا لمتغير الجنس. شمل البحث عينة مكونة من (187) طالبا وطالبة من طلبة الصفين الرابع والخامس الإعدادي، استخدم الباحثان أداتين جاهزتين الأولى لقياس الحرمان من عاطفة الأبوين والثانية لقياس السلوك العدائي، بعد أن جرى التحقق من صدقهما بطريقة الصدق الظاهري، وثباتهما بطريقة إعادة التطبيق للأداة الأولى والتجزئة النصفية للأداة الثانية، واستخدم الباحثان الاختبار التائي لعينة واحدة ومعامل ارتباط بيرسون للتوصل للنتائج التي أشارت إلى أن أفراد عينة البحث كانوا يشعرون بدرجة متوسطة بالحرمان من عاطفة الأبوين، كما بينت النتائج انتشار السلوك العدائي بدرجة متوسطة، وأظهرت النتائج ارتباط متغيري البحث ارتباطا موجبا ودالا إحصائيا عند مستوى (0.05). كما أشارت النتائج الى عدم وجود فرق ذي دلالة إحصائية في معامل الارتباط تبعا لمتغير الجنس. وفي ضوء النتائج قدم الباحثان مجموعة من التوصيات والمقترحات.The research aimed at measuring the level of parents emotional deprivation. and measuring the level of aggressive behavior in secondary school pupils. As well as identifying the relationship between the degree of parents emotional deprivation and aggressive behavior in the members of the research sample. The research involved a sample of (187) pupils, from fourth and fifth preparatory grades classes in Mosul, The researchers use two tools. The first to measure parents emotional deprivation, and the second to measure aggressive behavior. After the checking was depended on a face validity verified in a manner validity apparent. and endurance in a re-application of the first tool and the retail mid-term of the second tool. The researchers used (T test) for one sample and the Pearson correlation coefficient. to analyze the results which indicated that the sample felt the deprivation of parental affection to a middle degree. The results also indicate the spread of a moderately aggressive behavior. The results showed appositive link of research variables and statistically correlated at the level of (0.05).and that there was no statistically difference in correlation according to the variable of sex. In the light of the findings the researchers presented a set of recommendations and proposals.